Pemanfaatan Limbah Kertas Semen, Serat Bambu, dan Serat Fiber Sebagai Bahan Tambah Pembuatan Plafon Gypsum - Akbar, Agam Fauzie; Sentosa, Khalid Al Rasyid; H, Hartono; Fauziyah, Shifa (Universitas Diponegoro, 2023)
The ceiling is a part of building construction that serves as the ceiling of the building. The ceiling industry is an industry that easily keeps up with the times with various innovations produced. Therefore, with the innovation of bamboo fiber, fiber fiber and paper pulp as added materials to the gypsum ceiling, it can be optimized as raw material for making gypsum ceilings. The purpose of this study is to optimize cement paper waste, bamboo fiber waste and fiber fiber to optimize waste around the environment as gypsum ceiling added material to produce gypsum ceiling with better quality. The method used is research and experiments with job mix used is the addition of 0%, 1.5%, 2%, 2.5%, 3% cement pulp waste 0%, 1.5%, 2%, 2.5%, 3% bamboo fiber waste, , 0%, 1.5%, 2%, 2.5%, 3% fiber fiber. The results of the study can be seen that the highest flexural strength of 138.89 kgf / cm2 occurs in the percentage composition of 2.5% bamboo fiber, fiber fiber and cement pulp compared to the bending strength of normal variations, in the best water absorption how much in the composition of 1.5% fiber fiber with a value of 9.09% better than the normal ceiling, the best moisture content is in the composition of 2% bamboo fiber-cement pulp and 2.5% bamboo fiber, fiber fiber and cement pulp compared to normal ceiling. However, from the results of the price analysis, it can be seen that the variation in the percentage of 2.5% bamboo fiber, bamboo fiber and cement pulp requires a higher cost than the normal ceiling with a difference of Rp. 38.00.